Warburg-like Metabolic Reprogramming in Endometriosis: From Molecular Mechanisms to Therapeutic Approaches - Bo-Sung Kim; Bosung Kim; Seyeong Yoon; Wonyoung Park; Sung-Jin Bae; Jongkil Joo; Wonnam Kim; Ki-Tae Ha (Pharmaceuticals, 2025)
Endometriosis is a chronic gynecological disorder characterized by the presence of endometrial-like tissue outside the uterus, leading to inflammation, pain, and infertility. Emerging evidence indicates that endometriotic lesions exhibit cancer-like properties, including metabolic reprogramming marked by increased glucose uptake, enhanced Warburg’s effect, and altered mitochondrial function. These metabolic adaptations support cell survival under hypoxic conditions and contribute to immune evasion and sustained proliferation. This review summarizes current findings on the molecular mechanisms driving metabolic reprogramming in endometriosis, including the roles of mitochondrial dysfunction, hypoxia-inducible factor (HIF) signaling, the PI3K/AKT/mTOR pathway, inflammatory cytokines, and genetic and epigenetic regulators. In addition, we discuss therapeutic strategies targeting glycolytic pathways using both synthetic inhibitors and natural compounds, which represent promising non-hormonal options. Finally, we highlight the need for further preclinical and clinical studies to validate metabolic interventions and improve outcomes for patients with endometriosis.